Biogeochemical and ecohydrologic controls on arsenic mobilization in groundwater of the Okavango Delta - Enriquez, Hersy J. (Kansas State University, 2014)
The detrimental health effects of arsenic (As) contamination have motivated the study of As mobility around the globe. The variability in naturally occurring As concentration is due to variation in geology and climate. In arid environments with high evaporation, ecohydrology and As desorption under alkaline pH are thought to be responsible for high As concentrations. In reducing groundwater, on the other hand, microbial iron (Fe) reductive dissolution is known to release As into solution. In such environments, As-sulfide minerals precipitation and vegetation uptake could contribute to re-distribution of As. The Okavango Delta is an arid-zone wetland punctuated by ten of thousands of islands, and the reducing groundwater beneath these islands have dissolved As as high as 3000 µg•L[superscript]-1. Ecohydrologic controls are thought to contribute to the elevated As level; however dissolution of Fe-containing sediments has been proposed as the initial step in releasing As from sediment to the groundwater. To test the consistency of the hypothesized mechanisms, four islands were sampled in January 2013. The goal of this thesis is to: 1) provide more evidence on the zones of elevated As in groundwater of four islands, 2) gain understanding on the influence ecohydrology (i.e., evapotranspiration) on high As in groundwater, 3) evaluate the sediment of microbial community composition, and 4) gain new insights into the behavior of DOM along the groundwater flow path. The findings show zones of elevated As in all four islands. The ecohydrologic controls provide information on the location of high As and solute accumulation. Microbial analyses suggest DNA sequences collected were grouped within lineages that contain organisms capable of dissimilatory Fe reduction and sulfate reduction. This supports evidence from previous study that sulfide produced by microbial sulfate reduction is available for As-sulfide mineral formation. The variation of DOM characteristics could influence As solubility and reactivity. In addition, carbonate alkalinity and increase pH may contribute to As mobility further along the flow path. In this arid and reducing groundwater, we find that ecohydrologic and biogeochemical processes have a fundamental role in As mobility.
Keywords: Okavango Delta; Arsenic; Dissolved Organic Matter; Sulfate Reducing Bacteria; Groundwater; Environmental Engineering (0775)